1999
DOI: 10.1080/00222349908212441
|View full text |Cite
|
Sign up to set email alerts
|

A combined raman imaging and transmission electron microscopy study of blends of a deuterated linear polyethylene and a low-density polyethylene

Abstract: Local compositional variations in blends are examined using micro-Raman imaging. Raman images are compared with morphologies detected by transmission electron microscopy (TEM). In isothermally crystallized blends, with morphologies composed of clusters of crystals rich in deuterated linear polyethylene (DLPE) in a matrix of quenched material, the results from both techniques are comparable. These results show that compositional variations of about 30% can be detected by Raman imaging on a scale as small as 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…morphology of surface replicas for quenched LPE and BPE blends by transmission electron microscopy (TEM) was associated with liquid-liquid phase separation [3,4] it was later found by Micro-Raman imaging that the morphology could be explained by differences in nucleation densities and, therefore, crystallization effects on cooling. [5] In addition, research on phase segregation between deuterated LPE and BPE using small-angle neutron scattering (SANS) showed that blends fail to exhibit complete miscibility when branching content is greater than a certain value. [6][7][8] In the case of linear low density polyethylene (LLDPE) copolymers of a heterogeneous composition, phase segregation was proposed to occur in the melt among the species that differ mainly in branching content.…”
Section: Introductionmentioning
confidence: 99%
“…morphology of surface replicas for quenched LPE and BPE blends by transmission electron microscopy (TEM) was associated with liquid-liquid phase separation [3,4] it was later found by Micro-Raman imaging that the morphology could be explained by differences in nucleation densities and, therefore, crystallization effects on cooling. [5] In addition, research on phase segregation between deuterated LPE and BPE using small-angle neutron scattering (SANS) showed that blends fail to exhibit complete miscibility when branching content is greater than a certain value. [6][7][8] In the case of linear low density polyethylene (LLDPE) copolymers of a heterogeneous composition, phase segregation was proposed to occur in the melt among the species that differ mainly in branching content.…”
Section: Introductionmentioning
confidence: 99%
“…Though not marked in Fig. 7, lower intensities of the PES:PEES bands located around 1145 and 790 cm 21 were often observed with PES: PEES-Cl with a hole of 200 mm . No reproducible peak shift was noticed.…”
Section: Resultsmentioning
confidence: 83%
“…M icro-Raman spectroscopy allows for a lateral and in-depth resolution on the order of the m icrometer. [16][17][18][19][20][21] Infrared m icroscopy is also used, 23 although its spatial resolution of 8-10 mm constitutes a limiting factor. 19,20 The Raman technique is increasingly used for spatially-resolved characterization of various kinds of phase separated therm oplastic-thermoplastic blends.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations